Vegetable Seed Priming: a Low Cost, Simple and Powerful Techniques for Farmers’ Livelihood - Maiti, Ratikanta; Pramanik, Kalipada (International Journal of Bio-resource and Stress Management, 2023)
Seed priming is a simple, low-cost, low-risk intervention and powerful technique for improve seedling emergence, seedling vigour and yields of several field crops. There exist different priming techniques viz. Hydro-priming, Halo-priming, Osmo-priming and solid matrix priming. On-farm priming has been practiced on maize, rice wheat and other field crops as well as vegetable crops with success. With respect to vegetable crops, priming techniques have been adopted to study their effect on seedling vigor and agronomic traits including yield of tomato, chilli, cucumber and cabbage. It was observed that few priming technique improved seedling emergence percent, seedling vigor as well as agronomic traits including yield of the crop species although varying among species. It is clearly observed that in all the crops studied the priming techniques improved growth and yield of all the crops although the cultivars showed variation in responses to different treatments. In almost all the cases seedling vigor improves and the agronomic traits.